2019
DOI: 10.1002/cam4.1998
|View full text |Cite
|
Sign up to set email alerts
|

Real impact of liver cirrhosis on the development of hepatocellular carcinoma in various liver diseases—meta‐analytic assessment

Abstract: Background It is well known that the incidence of developing hepatocelluler carcinoma (HCC) is increased in liver cirrhosis of different etiologies. However, comparison of HCC incidence in various liver diseases has not yet been estimated. We surveyed this comparison. Methods The PubMed database was examined (1989‐2017) for studies published in English language regarding the prospective follow‐up results for the development of HCC in various liver diseases. A meta‐analysis was performed for each liver disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 132 publications
(153 reference statements)
2
92
0
Order By: Relevance
“…Although cirrhosis may be regarded as a premalignant stage, the development of HCC in cirrhosis requires additional and progressive preneoplastic stages as additional stepping stones towards HCC. 18 This spectrum of development can be crudely broken down into distinct stepwise progression events from injured, often cirrhotic, liver to focal patches of low-grade dysplastic nodules, then through high-grade dysplastic nodules onto HCC 19 (Fig. 1).…”
Section: General Concepts Surrounding the Mutational Events Leading Tmentioning
confidence: 99%
“…Although cirrhosis may be regarded as a premalignant stage, the development of HCC in cirrhosis requires additional and progressive preneoplastic stages as additional stepping stones towards HCC. 18 This spectrum of development can be crudely broken down into distinct stepwise progression events from injured, often cirrhotic, liver to focal patches of low-grade dysplastic nodules, then through high-grade dysplastic nodules onto HCC 19 (Fig. 1).…”
Section: General Concepts Surrounding the Mutational Events Leading Tmentioning
confidence: 99%
“…Studies have reported that 80–90% of patients with HCC present liver fibrosis or cirrhosis (El-Serag, 2011). A recent meta-analysis of studies in cirrhotic patients with five liver diseases (hepatitis B, hepatitis C, primary biliary cholangitis, autoimmune hepatitis, and non-alcoholic steatohepatitis) showed that the incidence of liver cancer is significantly increased when liver disease develops into cirrhosis, indicating that cirrhosis is one of the crucial risk factors for HCC (Tarao et al, 2019). Patients with liver cancer, with or without cirrhosis, show different clinical characteristics, including differences in tumor size and prognostic factors (Techathuvanan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cirrhosis can result in jaundice, asterixis, portal hypertension (leading to portocaval anastomoses such as esophageal varices, which are the most common acute cause of death), encephalopathy, and thrombocytopenia [ 11 ]. End-stage cirrhosis requires liver transplantation for survival and also increases the risk of HCC development by 45-fold (discussed further under “risk of progression”) [ 12 ].…”
Section: Histological Progressionmentioning
confidence: 99%